The applicability of the 'Japanese management style', to the South African context: Preliminary Research - Linda Human; Leonie Le Roux (South African Journal of Business Management, 1983)
This introductory study of the applicability of the 'Japanese management style' to the South African context highlights a number of important Issues relating to the study of Japanese economic progress and to the applicability of 'Japanese management methods to other contexts. It also questions the often-held assumption that the so-called 'Japanese methods' are so very different from those employed in the West.This article subsequently takes a look at the core workforce in Japan in relation to some research findings with regard to certain South African companies within which quality control circles are in use or are planned for the future. In so doing, it highlights certain problems relating not only to the delimitation of the 'Japanese' style but also its applicability to a context of cultural heterogeneity. In other words, this research questions the extent to which techniques of management which have proved successful in a relatively stable, equal, homogeneous and educated culture can be applied in a culturally and educationally heterogeneous society in which one particular group dominates the remainder.
Keywords: 650